Pedophilia and adult-child sex : a philosophical analysis - Kershnar, Stephen (Lexington Books, 2015)
"This book provides a philosophical analysis of adult-child sex and pedophilia. This sex intuitively strikes many people as sick, disgusting, and wrong. The problem is that it is not clear whether these judgments are justified and whether they are aesthetic or moral. By analogy, many people find it disgusting to view images of obese people having sex, but it is hard to see what is morally undesirable about such sex: here the judgment is aesthetic. This book looks at the moral status of such adult-child sex. In particular, it explores whether those who engage in adult-child sex have a disease, act wrongly, or are vicious. In addition, it looks at how the law should respond to such sex given the above analyses"--Publisher's description.